Sex in advertising : how it influences young men and women - Hultin, Marcus; Lundh, Erik (2004)
Companies make use of sexual appeal in advertising more now than ever. Very little research has been conducted of how the youth react to this and therefore, the purpose of this study is to gain a better understanding of how the youth perceive sex in advertising. More specifically, it deals with how the youth define and perceive sexual appeal in advertising. The study has a qualitative approach and the empirical data was gathered through two focus group interviews with students from Örnen high school in Luleå. The findings and conclusions of this study indicated that there are gender differences of how the youth define and react to sex in advertising. Young men tend to be more focused on physical attractiveness while young women focus more on other factors such as movement. Furthermore, our conclusions suggest that there are differences of how young women and men perceive sex in advertisement. Our findings suggest that young men are not as affected as young women concerning buying behavior and self-confidence by the sexual appeals in advertisements. Validerat; 20101217 (root)